ナンキョクオキアミ・カテコールオキシターゼの精製および特性 - OHSHIMA, Toshiaki; 大島, 敏明; オオシマ, トシアキ; OSHIMA, Toshiaki; Nagayama, Fumio (NIPPON SUISAN GAKKAISHI, 1980)
A catechol oxidase was isolated from the crude extract of the Antarctic krill, Euphausia superba, by a combination of ammonium sulfate treatment, ion exchange chromatography on DEAE-cellulose, and gel filtration on Sepharose 6B. The specific activity was increased about 36-fold from the supernatant of crude extract. The enzyme preparation was found to be homogeneous by polyacrylamide gel disc-electrophoresis. Optimum pH of the enzyme activity for catechol was found to be 6.5. Molecular weight of the enzyme was found to be 314, 000. One molecule was found to be composed of four subunits, and two of them had molecular weight of 75, 000 and the others 83, 000. Isoelectric point of the enzyme was pH 4.50. The activity was inhibited by potassium cyanide and sodium azide. Diethyldithiocarbamate did not inhibit the enzyme. The enzyme oxidized only a limited number of o-diphenols such as catechol and trihydroxy phenols such as pyrogallol. Monophenols such as L-tyrosine, the derivatives of L-tyrosine and L-dihydroxyphenylalanine (L-dopa) were not oxidized by the krill enzyme. In this respect, the enzyme of the krill was considered to be not tyrosinase (EC 1.14. 18.1 )but catechol oxidase (EC 1. 10. 3. 1). journal article